64 Introduction of safe space beds into great ormond street hospital. (23rd February 2023) - West, Ema-Mae; Oulton, Kate; Gee, Catherine; Walker, Alexander
Abstract : Background: Concerns about the care and treatment of people with learning disabilities attending acute hospitals have led to multiple inquiry's flagging system failures within the NHS. Furthermore, research by Oulton et al. (2018) has found an inequality in standards of healthcare for children and young people (CYP) with learning disabilities, including the need for adapted equipment and reasonable adjustments. The GOSH Learning Disability strategy strives to improve on quality of care and safety for all CYP and parents with Learning Disabilities and Autism coming into the trust. The safety risks reported from the current beds and the feedback from patients and families indicated a need for a better alternative. Aim: To present case studies of the benefits and challenges of introducing a specialist bed for CYP with learning disabilities and or autistic spectrum condition. Methods: The learning disability team undertook a review of available bed options. A trial of Safe Space bed was undertaken, to allow the team to assess the suitability of the beds for use. Bespoke product development was completed including considerations of infection control requirements, resuscitation accessibility, medication/line access, moving and handling needs, and appropriateness for tissue viability. Results: The team secured 6 new safe space beds which came into the trust in June 22. Preliminary data indicates these have been received well by CYP, families and staff, with reports of them meeting the child's safety and comfort needs. However, challenges associated with training, cleaning and storage have been identified. Conclusion: The introduction of new specialist beds are expected to provide a safe, sensory, and comforting space for children and young people in the trust and we anticipate our learning can inform other healthcare providers about the potential rewards and challenges.